Efficacy of antibacterial envelope in prevention of cardiovascular implantable electronic device infections in high-risk patients: A systematic review and meta-analysis. (15th September 2020) - Ullah, Waqas; Nadeem, Nayab; Haq, Shujaul; Thelmo, Franklin L.; Abdullah, Hafez M.; Haas, Donald C.
Abstract: Background: Limited evidence is available to determine the efficacy of an antibacterial enveloped (AE) cardiovascular implantable electronic device (CIED). Objective: To assess if the use of antibacterial enveloped devices in high-risk patients are associated with lower chances of major CIED infections and mortality compared to non-enveloped devices. Methods: A comprehensive literature search on multiple databases was performed. The relative odds ratio (OR) of major CIED infection and mortality was calculated using a random-effect model. Results: A total of six studies consisting of 11, 897 patients, were included; 5844 with an AE-CIED and 6053 with conventional CIED. In the pooled cohort, patients with AE-CIED had a 66% lower odds of major CIED infection (OR 0.34, 0.13, 0.86, CI 95%, p = 0.02) compared to CIED. Propensity matched analysis showed a 71% lower odds of major infection in the AE-CIED group (OR 0.29, 95% CI 0.10–0.82, p = 0.02). Stratified analysis based on the type of study (retrospective vs. prospective) and duration of follow up (6 months vs. greater than six months) also showed numerically lower infection odds in the AE-CIED. Similarly, the relative odds of mortality were lower in patients with AE-CIED (OR 0.55, 95% CI 0.16–1.91, p = 0.34) compared to CIED patients; however, this difference was statistically non-significant. Conclusion: In high-risk patients, AE-CIED might offer lower odds of CIED infections. It has numerically lower (45%) but statistically non-significant odds of mortality if used in conjunction with the standard infection prevention protocol. More large scale studies and long-term follow-ups are required to validate our findings. Highlights: Antibacterial enveloped cardiovascular implantable electronic device (AE-CIED) represent advances over conventional devices. AE-CIED significantly reduces the odds of pocket and device infection. AE-CIED confers numerical advantage of lower infection related mortality over CIED.